Analisis Potensi Yang Dimiliki Stadion Patra Jaya Plaju Sebagai Destinasti Wisata Berkelanjutan Untuk Masyarakat Kota Palembang - Lili Anggraini; Nurvia Nathasya (CV. ITTC INDONESIA, 2023)
Patra Jaya Stadium Palembang City. The stadium that was established in the 90s and was popular in its day today has become an abandoned stadium without maintenance. The stadium located in the Plaju area, Palembang City has the potential to be very worthy of development. This is because there is a lot of history carved about football in the city of Palembang. The purpose of this study is to determine the potential of Patra Jaya Plaju Stadium as a sustainable tourism destination for the people of Palembang. The method in this study is by qualitative descriptive method. From the research above, it can be concluded that Patra Jaya Stadium has the potential to be developed as an environmentally friendly sustainable tourism location, while jointly developing Patra Jaya Stadium, Plaju Palembang which at this time still cannot be called a tourist attraction destination.